Pengaruh Motivasi Belajar terhadap Kemampuan Self-Directed Learning Dimoderasi oleh Aksesibilitas Teknologi Digital pada Mahasiswa FKIP Universitas Sebelas Maret Surakarta - Setyo Laksono; Kristiani Kristiani; Dini Octoria (Journal on Education, 2023)
The aim of this research is to find out whether learning motivation influences self-directed learning skill FKIP students at Sebelas Maret University, Surakarta, find out whether digital technology accessibility can moderate the relationship between learning motivation and self-directed learning skill FKIP student at Sebelas Maret University, Surakarta. The research method used is quantitative with a population of FKIP Sebelas Maret University Surakarta students class 2019, 2020, 2021 and 2022. The sampling technique uses simpel random sampling with a sample size of 264 respondents. Data collection uses documentation and questionnaires and data analysis uses simple linear regression analysis and moderated regression analysis. The results of this research are (1) There is a positive and significant influence between learning motivation and self-directed learning skill FKIP students at Sebelas Maret University, Surakarta with a calculated t value > t table (26.473 > 1.96) and a significance value of 0.000 < 0.05. (2) Digital technology accessibility variables cannot moderate the relationship between learning motivation and self-directed learning skill FKIP student at Sebelas Maret University, Surakarta with a score of sig. interaction between learning motivation and digital technology accessibility 0.195 > 0.05.